Comparative economic analyses of patient safety improvement strategies in acute care: a systematic review. Issue 6 (22nd April 2012) - Etchells, Edward; Koo, Marika; Daneman, Nick; McDonald, Andrew; Baker, Michael; Matlow, Anne; Krahn, Murray; Mittmann, Nicole
Abstract : Background: The objective was to systematically review comparative economic analyses of patient safety improvements in the acute care setting. Methods: A systematic review of 15 patient safety target conditions and six improvement strategies was conducted. The authors searched the published literature through Medline (2000–November 2011) using the following search terms for costs: 'costs and cost analysis', 'cost-effectiveness', 'cost' and 'financial management, hospital'. The methodological quality of potentially relevant studies was appraised using Cochrane rules of evidence for clinical effectiveness in quality improvement, and standard economic methods. Results: The authors screened 2151 abstracts, reviewed 212 potentially eligible studies, and identified five comparative economic analyses that reported a total of seven comparisons based on at least one clinical effectiveness study of adequate methodological quality. Pharmacist-led medication reconciliation to prevent potential adverse drug events dominated (lower costs, better safety) a strategy of no reconciliation. Chlorhexidine for vascular catheter site care to prevent catheter-related bloodstream infections dominated a strategy of povidone-iodine for catheter site care. The Keystone ICU initiative to prevent central line-associated bloodstream infections was economically dominant over usual care. Detecting surgical foreign bodies using standard counting compared with a strategy of no counting had an incremental cost of US$1500 (CAN$1676) for each surgical foreign body detected. Several safety improvement strategies were less economically attractive, such as bar-coded sponges for reducing retained surgical sponges compared with standard surgical counting, and giving erythropoietin to reduce transfusion requirements in critically ill patients to avoid one transfusion-related adverse event. Conclusions: Five comparative economic analyses were found that reported a total of seven comparisons based on at least one effectiveness study of adequate methodological quality. On the basis of these limited studies, pharmacist-led medication reconciliation, the Keystone ICU intervention for central line-associated bloodstream infections, chlorhexidine for vascular catheter site care, and standard surgical sponge counts were economically attractive strategies for improving patient safety. More comparative economic analyses of such strategies are needed.